2022
DOI: 10.1200/jco.21.01217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Risk Multiple Myeloma With a Plasma Cell Leukemia-Like Transcriptomic Profile

Abstract: PURPOSE Primary plasma cell leukemia (pPCL) is an aggressive subtype of multiple myeloma, which is distinguished from newly diagnosed multiple myeloma (NDMM) on the basis of the presence of ≥ 20% circulating tumor cells (CTCs). A molecular marker for pPCL is currently lacking, which could help identify NDMM patients with high-risk PCL-like disease, despite not having been recognized as such clinically. METHODS A transcriptomic classifier for PCL-like disease was bioinformatically constructed and validated by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 104 publications
(130 reference statements)
4
24
1
Order By: Relevance
“…Furthermore, in patients with matched bone marrow (BM) and peripheral blood samples, CTCs had a significantly higher PCL-like transcriptomic score compared with BM plasma cells. 14 This is in line with prior data from Paiva et al, 19 who had demonstrated CTCs to have higher clonogenic potential compared with paired BM plasma cells. This further adds to the biological plausibility behind CTCs being an important prognostic factor in myeloma.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…Furthermore, in patients with matched bone marrow (BM) and peripheral blood samples, CTCs had a significantly higher PCL-like transcriptomic score compared with BM plasma cells. 14 This is in line with prior data from Paiva et al, 19 who had demonstrated CTCs to have higher clonogenic potential compared with paired BM plasma cells. This further adds to the biological plausibility behind CTCs being an important prognostic factor in myeloma.…”
supporting
confidence: 87%
“…20 Furthermore, CTCs in myeloma are quiescent and express CD44, an antigen associated with cancer stem cells. 19,20 Hofste op Bruinink et al 14 demonstrated that genes related to cell adhesion, tumor suppression, proliferation, RNA splicing, cell migration, and DNA damage control were differentially expressed in patients with high CTC burden. Using a transcriptomic classifier, they identified 10% of patients with newly diagnosed myeloma who presented with PCL-like malignant plasma cells in blood and BM regarding transcriptional, cytogenetics, and clinical features, and had significantly worse outcomes.…”
mentioning
confidence: 99%
See 3 more Smart Citations